2002
DOI: 10.1016/s0886-3350(01)01275-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracorneal rings to correct corneal ectasia after laser in situ keratomileusis

Abstract: Intacs intrastromal corneal rings used as a mechanical device may alter the biomechanical properties of the cornea for the correction of iatrogenic keratectasia and the associated residual myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 10 publications
5
73
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10]12,15,32,33 The procedure is generally safe, with only rare cases of corneal infections. 34 Morphologic studies have shown local stromal reaction with keratocyte activation, lipid accumulation, moderate fibrosis, mild epithelial changes, and formation of new collagen and hypocellular scars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10]12,15,32,33 The procedure is generally safe, with only rare cases of corneal infections. 34 Morphologic studies have shown local stromal reaction with keratocyte activation, lipid accumulation, moderate fibrosis, mild epithelial changes, and formation of new collagen and hypocellular scars.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs mostly after LASIK but was also described after surface excimer laser ablation (photorefractive keratectomy). [14][15][16] It involves severe refractive changes mostly occurring several years after the surgery, which are caused by thinning and sagging of the corneal profile, similar to keratoconus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 FDA-approved 3 intrastromal corneal ring segments (ICRS) have been found beneficial for the treatment of KC and corneal ectasia following refractive surgery [4][5][6] as they flatten and regularize the cornea by means of an arc shortening effect. 7 The most common types of ICRS used in clinical practice are Intacs (Addition Technology, Inc., Sunnyvale, CA, USA) and Ferrara rings (Ferrara Ophthalmics, Brazil).…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are several options to treat corneal ectatic diseases before a corneal transplant. A surgical alternative method to stabilize or delay the progression of the ectatic disease involves the implantation of intracorneal ring segments [3][4][5]. According to the postulates of Barraquer [6] and Blavatskaya [7], the intracorneal ring segments implanted in the corneal stroma lead to a flattening on the corneal surface.…”
Section: Introductionmentioning
confidence: 99%